2014
DOI: 10.1039/c4tb01390e
|View full text |Cite
|
Sign up to set email alerts
|

Progress in heparin and heparin-like/mimicking polymer-functionalized biomedical membranes

Abstract: Research into the design of heparin and heparin-like/mimicking polymer-functionalized biomedical membranes is of tremendous interest to the biomedical sector in particular and is driven by potential diverse biomedical applications such as blood purification, artificial organs and other clinical medical devices. In this review, we highlight the progress of the recent research and propose potential biomedical applications in the fields of surface heparinization and the heparin-inspired modification of polymeric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
117
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(120 citation statements)
references
References 172 publications
(193 reference statements)
3
117
0
Order By: Relevance
“…However, its intensity vanishes at higher blend composition of PU i.e., the 70/30 and 60/40 membranes (Fig. 54,36 This result establishes the better compatibility between the individual polymers. Pure PU membrane ( Fig.…”
Section: Ftir Analysis Of the Pan/peg Blend Membranesmentioning
confidence: 59%
See 1 more Smart Citation
“…However, its intensity vanishes at higher blend composition of PU i.e., the 70/30 and 60/40 membranes (Fig. 54,36 This result establishes the better compatibility between the individual polymers. Pure PU membrane ( Fig.…”
Section: Ftir Analysis Of the Pan/peg Blend Membranesmentioning
confidence: 59%
“…Zavastin et al 31 reported the successful application of PU/CA blend membranes in wastewater treatment in the textile industry. [34][35][36] In addition, better antifouling and antithrombotic properties using PES/PU composite membranes during dialysis was carried out by Yin et al 37 A recent report by Roy et al 38 showed that a PSF/PVP/PEG blend membrane was found to have adequate cyctocompatibility and blood compatibility for hemodialysis. The ux and protein rejection were increased for the blend ultraltration (UF) membranes with dimethylacetamide (DMAc) when compared to dimethylformamide (DMF) as a solvent.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31] The purified platelets are used as the models for platelet capture on the patterned surface. [28][29][30][31] The purified platelets are used as the models for platelet capture on the patterned surface.…”
Section: Cell Capture On the Patterned Surfacementioning
confidence: 99%
“…Therefore, much attention has been paid to developing new synthetic macromolecules to replace heparin . It is believed that the bioactivity of heparin is mainly caused by the active sequence of pentasaccharide, molecular conformation, and ionic functional groups (sulfonate, sulfamide, and carboxylate) . Recent studies indicated that polymers with sulfonate, sulfamide, and/or carboxylate as pendant groups possess partial functions of heparin, such as anticoagulant ability and cell affinity .…”
Section: Introductionmentioning
confidence: 99%